Examination Of Mobbing Behaviors Experıenced By The Personnel Working At Youth Services And Provincial Directorates Of Sports, - Hacıcaferoğlu, S., Gündoğdu C., Yücel, A. S., Acet, M., (My University, 2012)
The purpose of this research is to examine mobbing behaviors experienced by the personnel working at Youth Services and Provincial Directorates of Sports according to their sex, age, marital status, occupational seniority and graduated school. The research is such made by using general scanning model. The personnel working at the district and provincial offices of Youth Services and General Directorate of Sports constitute the population of the research and 325 personnel working at Youth Services and Provincial Directorates of Sports selected randomly from the population in 25 provinces constitute the sample of the research. The data regarding mobbing actions experienced by the personnel was collected by using “Negative Acts Questionnaire” (NAQ). “Negative Acts Questionnaire” (NAQ) was developed by Einarsen and Raknes (1) and adapted to Turkish by Cemaloglu (2). Cronbach Alpha reliability coefficient of the subjected scale was re-calculated and determined to be 0,89. During the analysis of data frequency (f), percentage distribution (%), arithmetic average (x), -t and F tests were used and data were analyzed by means of SPSS 15,00 packaged software. Significance level was accepted as 0.5 in order to determine whether a difference exists between the variants applied in the questionnaire. As a result of our research it was determined that 44% of the personnel working in GHSİM (Youth Services and General Directorate of Sports) suffered mobbing behaviors. When the questionnaire results are analyzed it is seen that women exposed more mobbing behaviors comparing to men, those between 21-30 age group exposed more mobbing behaviors comparing to other age groups, those married exposed more mobbing behaviors comparing to single and divorced, those having 1-10 years of seniority exposed more mobbing behaviors comparing to those having other seniorities, those having bachelor’s degree and associate degree exposed to more mobbing behaviors comparing to other graduates. It was determined that there is a significant difference between mobbing experiencing levels according to sex, age, occupational seniority and graduated school of the GHSİM personnel and no significant difference according to marital status variant.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Mobbing; Psychological Violence; Youth Services and Provincial Directorate of Sports